2018
DOI: 10.4103/eus.eus_15_17
|View full text |Cite
|
Sign up to set email alerts
|

A tertiary care hospital's 10 years' experience with rectal ultrasound in early rectal cancer

Abstract: Background and Objectives:Rectal endoscopic ultrasound (RUS) has become an essential tool in the management of rectal adenocarcinoma because of the ability to accurately stage lesions. The aim of this study was to identify the staging agreement of early RUS-staged rectal adenocarcinoma with surgical resected pathology and ultimately determine how this impacts the management of early rectal cancer (T1–T2).Methods:Retrospective chart review was performed from November 2002 to November 2013 to identify procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, the visualization of the anorectosigmoid region during endoscopy of the patient prior to treatment, identifies other colorectal diseases that may be contributing to the symptoms such as bleeding, especially colorectal neoplasia. [ 63 , 64 , 65 ] In the United States, a cohort study based on blood in the stool reported that the incidence of diverticulosis, polyps or multiple polyps, mucosal abnormalities/colitis, tumors, and solitary ulcers were significantly increased in the patients undergoing endoscopy. [ 66 ] In addition, anorectal diseases such as hemorrhoids are very common in patients with intestinal diseases.…”
Section: Advantages Of Endoscopic Hemorrhoid Treatmentmentioning
confidence: 99%
“…Finally, the visualization of the anorectosigmoid region during endoscopy of the patient prior to treatment, identifies other colorectal diseases that may be contributing to the symptoms such as bleeding, especially colorectal neoplasia. [ 63 , 64 , 65 ] In the United States, a cohort study based on blood in the stool reported that the incidence of diverticulosis, polyps or multiple polyps, mucosal abnormalities/colitis, tumors, and solitary ulcers were significantly increased in the patients undergoing endoscopy. [ 66 ] In addition, anorectal diseases such as hemorrhoids are very common in patients with intestinal diseases.…”
Section: Advantages Of Endoscopic Hemorrhoid Treatmentmentioning
confidence: 99%
“…ERUS has been proposed to exhibit superior accuracy in early disease staging when compared to MRI, albeit with reduced precision in assessing lymph node involvement. Conversely, MRI demonstrates superior accuracy in assessing lymph node status compared to ERUS [9,10].…”
Section: Patient Selectionmentioning
confidence: 98%
“…Endo-rectal ultrasound has been suggested to offer a higher accuracy in staging early disease compared to MRI, however offers poorer accuracy for lymph node assessment. The converse is suggested to be true for MRI scanning[ 7 , 8 ]. Both modalities were suggested to over-stage early T1/T2 disease and showed poor differentiation between the two[ 9 ].…”
Section: Staging Of Rectal Cancer and Definition Of Early Diseasementioning
confidence: 99%